Public debt of Ukraine: dynamics, structure, management methods - But, Tetiana; Mamotenko, Daria; Zaytseva, Valentyna (Management and Entrepreneurship: Trends of Development, 2020)
The paper studies the dynamics, structure, methods of Ukraine’s public debt management and identifies the constituent elements of the public debt management mechanism. The current trends of Ukraine’s debt policy are analyzed and its macroeconomic consequences are determined. It is established that public debt management is one of the key factors in ensuring macroeconomic stability in the country. According to the results of the study, the nature of the debt problem depends on the country’s budget capacity, the state of its foreign exchange reserves, and, accordingly, on the stability of the national currency, interest rates, investment climate, the behavior of all segments of the financial market. It is established that the main problem of public debt management lies in ensuring the solvency of the state, the real sources of public debt repayment. It was found that the most statistically significant factor influencing the size of Ukraine’s external debt is GDP growth. It is justified that in order to reduce the amount of the country’s external liabilities and increase GDP, it is necessary to resort to domestic borrowings as much as possible. It is proposed to use the foreign experience of developed countries in Western Europe and the United States, which resort to external borrowings only when there is a stable GDP growth. The study found that countries do not set the goal of reducing debt to zero, but recognize the need to reduce it to a certain level of sustainability, which depends on economic growth, interest rates, due to which countries occupy a certain place in domestic and foreign markets. It is noted that Ukraine’s current credit ratings should be raised through fiscal policy and reforms. The results of the study highlight the priority areas for implementing the medium-term public debt management strategy for 2019 – 2022. JEL Classification: R58.